ANALISIS STRATEGI ALTERNATIF PEMASARAN HOTEL VILA OMBAK DALAM SITUASI COVID-19 - Arief Astriawan; Erri Supriyadi; I Wayan Nuada; Dimas Eka Pratama (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to describe an alternative marketing strategy at the Gili Trawangan Villa Hotel in the Covid 19 situation. This type of research is descriptive qualitative. The writing method used in this research is to combine field findings and theory. Data collection techniques such as observation, interviews, documentation, previous studies and the official website. This study describes the marketing strategy; segmenting, targeting and positioning with Strengths Weaknees Opportunities Threats (SWOT) analysis. The results of this study indicate that the strategy is carried out by changing the direction of the market segment from the overseas market with the criteria for the middle and upper segment to be multi-segment. Likewise with the targeting of foreign tourists to domestic tourists. Hotel Vila waves also positions itself as an international hotel that provides one stop leisure services. This study concludes that the strategy adopted is a win-win solution for all parties.